Jual Beli Pupuk Kotoran Hewan Perspektif Mazhab Syafi’i - Fatih, Moh. Khoirul (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2022)
The sale and purchase of manure raises pros and cons among the Muslim community, because it is considered not in accordance with the pillars and conditions of buying and selling. However, seeing the high price of inorganic fertilizers (chemical) forced them to continue to use the existing manure as an ingredient in fertilizing the soil. This issue has raised many questions about how the certainty of Islamic law in responding to the phenomenon of society. Some scholars argue that buying and selling must use sacred items and are not classified as unclean, so the sale and purchase of unclean goods is considered invalid. Willingness to understand Imam Shafi'i is the main key in the practice of buying and selling. In addition, Imam Syafi'i also emphasizes the value of the benefits contained in the goods being traded. The practice of buying and selling animal manure can be said to have fulfilled the requirements and the pillars of buying and selling, namely the benefits for the community. However, the Mazhab Syafi’i still does not allow the practice of buying and selling fertilizers made from animal waste. In the Shafi'i school, the issue of buying and selling animal manure is offered a solution that the practice is not classified as a buying and selling practice (muamalah), but by isqath al-haq (aborting rights). The trick is sighat (speech) the contract is not a sale and purchase contract but naqlul yad (change of hands), or in another language the exchange of goods.